Impact of footwear bending stiffness and torsional stiffness on ankle biomechanics during handball specific fake-and-cut manoeuvres - Bagehorn, T.; Bill, K.; Mai, P.; Krosshaug, T.; Kersting, U. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
In this study, the impact of footwear bending stiffness on ankle and foot biomechanics during indoor fake-and-cut manoeuvres was investigated. Footwear, along with torsional and bending stiffness, are hypothesized to influence the risk of ankle sprain injury. In this study, a mobile, pneumatically driven cantilever rig was used to quantify these footwear characteristics. Following this, participants executed fake-and-cut movements wearing their habitual footwear, while motion capture and force plate data were recorded. Utilizing machine learning clustering algorithms, participants were grouped based on their footwear stiffness. Subsequent SPM analysis revealed lower forefoot dorsiflexion and increased forefoot inversion in the stiff group. These findings underscore the need for further research on the interaction between shoe properties and injury risk indicators.